Pengaruh EM4 dan Jarak Tanam terhadap Pertumbuhan dan Hasil Tanaman Stevia (Stevia rebaudiana Bertoni) dengan Irigasi Tetes - Ila Wasi'atul Mustabsyiroh; Arthur Frans Cesar Regar (Berkala Ilmiah Pertanian, 2023)
The purpose of this study was to determine the effect of stevia plant growth and yield on differences in EM4 concentrations and combinations with three different spacings. The experimental design used was a factorial randomized block design (RBD) with two research factors. The first factor was the EM4 concentration which consisted of 4 levels, namely A0 = 0% EM4 concentration, A1 = 25% EM4 concentration, A2 = 50% EM4 concentration, and A3 = 75% EM4 concentration. The second factor was the use of three different spacings, namely 25 cm x 25 cm, 30 cm x 30 cm, and 40 cm x 40 cm. The observation variables used in this study were plant height, number of leaves, fresh leaf weight, plant fresh weight, leaf dry weight, and root length. The data analysis used was ANOVA analysis of variance by conducting the F test at the ANOVA level α = 0.05. The F test was conducted to determine whether there was an effect of EM4 and spacing on the growth and yield of stevia plants. If the F-count is greater than the F-table, it indicates that there is a significant difference, then a follow-up DMRT test is performed with a p = 0.05 confidence level. The results showed that there was an interaction between the various spacings and the application of EM4 which had a highly significant effect on the variable plant height observed and a significantly different effect on the number of leaves observed. The single factor of the various plant spacings had highly significant different effects on the observed root length variables, as well as significantly different effects on the number of leaves, plant height, leaf fresh weight, plant fresh weight, and dry weight. leaf. The single factor EM4 had a significantly different effect on the variable plant height and number of leaves observed. Treatment distance of 30 cm x 30 cm (L1) and 50% EM4 concentration (A2) gave the best effect.